In vitro antimicrobial activity of non-traditional therapies for infectious endometritis in mares - Mazzuchini, Mariana P. [UNESP]; Lisboa, Fernando Paixão [UNESP]; de Castro, Jessica I.; Alvarenga, Marco A. [UNESP]; Segabinazzi, Lorenzo G. T. M.; Canisso, Igor F. (Wiley, 2024)
Background: Endometritis is the leading cause of subfertility in horses, and it is a clinical problem where historically antibiotics have not always been used with prudent justification. Because of this, alternative therapies to treat endometritis are necessary for the rational use of antibiotics. Objectives: To assess the in vitro antimicrobial activity of non-traditional therapies commonly used in clinical practice against microorganisms causing infectious endometritis in mares. Study design: In vitro experiments. Methods: A microdilution technique was performed to determine the minimum inhibitory concentrations (MIC) of 50%, 90% and 100% of microorganisms and the percentage of inhibition (PI) of each therapy against each microorganism (Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus and Candida sp.). The MIC 50% and 90% were determined using non-linear regression, while MIC 100% was assessed using the resazurin dye technique. The serial PI was evaluated for each therapy using a spectrophotometer. Results: All the therapies demonstrated a PI higher than positive controls for all microorganisms (p < 0.05); however, the only therapies that presented MIC 100 values were hydrogen peroxide and platelet-rich and -poor plasma. Main limitations: In vivo, safety and treatment efficacy were not tested. Conclusion: Hydrogen peroxide and platelet-rich and -poor plasma might be alternatives to traditional therapies for endometritis to support a reduction in antibiotic use.
Keywords: antibiotics; bacteria; fungus; horse; infection; subfertility